Effects of Environmental Temperature on the Dynamics of Ichthyophoniasis in Juvenile Pacific Herring (Clupea pallasii) - Gregg, Jake L. (Hindawi Publishing Corporation, 2011)
The effects of temperature and infection by Ichthyophonus were examined in juvenile Pacific herring (Clupea pallasii) maintained under simulated overwinter fasting conditions. In addition to defining parameters for a herring bioenergetics model (discussed in Vollenweider et al. this issue), these experiments provided new insights into factors influencing the infectivity and virulence of the parasite Ichthyophonus. In groups of fish with established disease, temperature variation had little effect on disease outcome. Ichthyophonus mortality outpaced that resulting from starvation alone. In newly infected fish, temperature variation significantly changed the mortality patterns related to disease. Both elevated and lowered temperatures suppressed disease-related mortality relative to ambient treatments. When parasite exposure dose decreased, an inverse relationship between infection prevalence and temperature was detected. These findings suggest interplay between temperature optima for parasite growth and host immune function and have implications for our understanding of how Ichthyophonus infections are established in wild fish populations.